Antley-Bixler Syndrome: A Case Report and Literature Review - Hermanto Hermanto; Irwan Taufiqur Rachman (Indonesian Journal of Obstetrics & Gynecology Science, 2020)
Sindroma Antley-Bixler pertama kali dikemukakan oleh Ray Antley dan David Bixler tahun 1975. Sindroma ini jarang dan berhubungan dengan kelainan perkembangan tulang dan kartilago sehingga sering disebut multisynostotic osteodysgenesis syndrome. Craniosynostosis dan synostosis radiohumeral merupakan temuan yang paling konsisten. Penyebab sindroma ini belum jelas, diduga karena adanya mutasi genetik.Laporan kasus:Seorang ibu 22 tahun G2P1A0 dirujuk ke poliklinik obstetri dan ginekologi RSUP dr.Sardjito pada usia kehamilan 32-33 minggu untuk pemeriksaan antenatal dengan kecurigaan fetal craniosynostosis dan ventriculomegaly. Pada usia kehamilan 38 minggu, bayi lahir dengan craniosynostosis, ocular hypertelorism, disertai syndactily digiti II-IV pedis dextra et sinistra dengan diagnosis sementara sindroma Apert. Pemeriksaan penunjang yakni MSCT scan kranial dan foto rontgen regio artikulatio cubiti anteroposterior dan lateral menunjukan adanya craniosynostosis dan synostosis radioulna dan radiohumeral bilateral mengarahkan diagnosis sindroma Antley-Bixler. Bayi dipulangkan setelah 24 hari perawatan. Saat ini bayi masih menjalani perawatan berkala di instalasi rawat jalan ilmu kesehatan mata dan bedah saraf RSUP Dr. Sardjito  Kesimpulan: Laporan kasus ini bertujuan untuk membahas penegakan diagnosis, tatalaksana yang telah dilakukan dan rencana tatalaksana yang akan datang.  Kata kunci : Sindroma Antley-Bixler, craniosynostosis, synostosis radiohumeralAntley-Bixler Syndrome: A Case Report and Literature Review AbstractAntley-Bixler syndrome (ABS) was first described by Ray Antley and David Bixler in 1975. The syndrome is rare and characterized by abnormalities of bone and cartilage development (“syndrome of multisynostotic osteogenesis”). Craniosynostosis and radiohumeral synostosis are the most consistent findings. The cause of this syndrome is unclear, but genetic mutations are suspected.Case report: A 22-year-old female G2P1A0 was referred to the obstetrics and gynecology outpatient clinic at RSUP Dr. Sardjito at 32-33 weeks of gestation for antenatal care and further evaluation due to suspected fetal craniosynostosis and ventriculomegaly. At 38 weeks’ gestation, the baby was born with craniosynostosis, ocular hypertelorism, and syndactily digiti II-IV pedis dextra and sinistra, suspected Apert syndrome. Further investigation by using radiologic examination (cranial MSCT scan and X-ray at anteroposterior and lateral articulation cubital) revealed craniosynostosis, bilateral radioulna and radiohumeral synostosis, directed the diagnosis to Antley-Bixler syndrome. The baby was discharged after 24 days of hospitalization. Currently, the baby is still undergoing regular evaluation and treatment at the Ophthalmology and Neurosurgery outpatient departments at RSUP Dr. SardjitoConclusion: The aim of this case report is to discuss how to diagnose this syndrome and the management that had been done and further plans.